Dexmedetomidine versus Dexamethasone as an Adjuvant to Ropivacaine in Transversus Abdominis Plane Block in Infraumbilical Surgeries for Postoperative Analgesia: A Randomised Clinical Study - Anupama Kumari; Aarjvi Patel; Payal Berawala; Sara Mary Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Postoperative pain due to abdominal wall incision in infraumbilical surgeries can negatively impact surgical outcomes and increase the risk of complications. Effective postoperative analgesia facilitates rehabilitation and recovery. The Transversus Abdominis Plane (TAP) block is a regional analgesic technique that blocks the nerves supplying the anterolateral abdominal wall (T7-L1). Adjuvants like dexamethasone and dexmedetomidine added to local anaesthetics can prolong the duration of the block. Aim: To compare the duration of analgesia (the time of first rescue analgesia) and the quality of pain relief, as assessed by the Visual Analogue Scale (VAS), between dexmedetomidine and dexamethasone as adjuvants to ropivacaine in the TAP block for infraumbilical surgeries. The secondary objective was to compare postoperative haemodynamic changes and side effects. Materials and Methods: In this randomised double-blinded prospective clinical study, conducted in the Department of Anaesthesia, Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre (SBKS MIRC), Piparia, Vadodara, Gujarat, India from March 2023 to September 2024. 80 patients of American Society of Anaesthesiologists (ASA) I and II, aged 18-60 years, undergoing elective infraumbilical surgeries (open abdominal hysterectomy and open bilateral inguinal hernia repair) under spinal anaesthesia were randomly allocated into two groups of 40 patients each. Group-R1 received 0.2% ropivacaine 3 mg/kg plus dexamethasone 0.1 mg/kg, while Group-R2 received 0.2% ropivacaine 3 mg/kg plus dexmedetomidine 1 μg/kg in a bilateral TAP block. The total volume was made up to 50 mL with normal saline. Postoperative pain was assessed using VAS scores. The time to first rescue analgesia demand and haemodynamic parameters were recorded. Results: The mean age of the study participants was 40.15±7.46 years (Group-R1) and 39.5±5.59 years (Group-R2). Demographic data, type of surgery, and duration of surgery were comparable between the two groups. VAS scores were significantly lower in Group-R2 compared to Group-R1 at all time points up to six hours postoperatively (p<0.0001). The mean duration of analgesia was significantly longer in Group-R2 (308.18±12.3 minutes) compared to Group-R1 (239.78±14.23 minutes) (p<0.0001). Haemodynamic parameters were comparable between the groups, with no significant side effects observed. Conclusion: Dexmedetomidine 1 μg/kg as an adjuvant to 0.2% ropivacaine in the TAP block provided a longer duration of analgesia and better quality of pain relief compared to dexamethasone 0.1 mg/kg for postoperative analgesia in infraumbilical surgeries.